KAJIAN SPASIAL KERUSAKAN EKOSISTEM TERUMBU KARANG UNTUK PENGELOLAAN LINGKUNGAN DI TELUK JAKARTA - , BAYU PRAYUDHA, S.SI; , Prof. Dr. Totok Gunawan, M.S., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Covering an area of 58% of coral reefs in the world and more than 80% in Southeast Asia has threatened by various human activities. Human activities that threaten the coral reefs include coastal development, marine pollution, destructive fishing, and inland pollution/sedimentation. Coral reefs in Jakarta Bay as the gateway to the State Capital are threatened also by such human activities. Therefore, there should be good environmental management efforts to maintain and preserve it. Spatial analysis can provide a picture of the region as a whole (holistic), so it can be used in the environmental management efforts. This research aims to develop spatial databases prototype, determine the level of human activity threats on coral reefs as well as the damage, and determine the strategy of environmental management in Jakarta Bay. The method used in this study is the spatial ecological approach with Geographic Information System (GIS) modeling. âReef at Riskâ model that developed by World Resources Institute with some modifications used to assess the levels of threat to coral reefs. Environmental management strategies of coral reefs in Jakarta Bay determined by considering the levels of human activities threat, the condition/health of coral reefs, waters suitability for coral reefs, as well as socio-economic conditions of society. The results of this study are: 1) Prototype of the spatial database of coral reefs environment in Jakarta Bay, 2) The threat levels of human activities to coral reef in the Jakarta Bay has âmediumâ and âhighâ category. The percentage area of coral reefs in each category are 33.07% and 66.93%, 3) The analysis of coral reefs damage by considering the condition of coral reefs and threats from human activities, produced two risk classes of coral reefs damage in Jakarta Bay, the classes are âmedium riskâ and âhigh riskâ. The percentage area of coral reefs in each classes are 60.69% and 39.31%, 4) Based on spatial analysis, the study area can be divided into three management areas that focused on efforts to public awareness, improved surveillance, recovery, utilization, and restraint.